The Effects of SEA0400 on Ca2+ Transient Amplitude and Proarrhythmia Depend on the Na+/Ca2+ Exchanger Expression Level in Murine Models - Nils Bögeholz; Jan S. Schulte; Sven Kaese; B. Klemens Bauer; B. Klemens Bauer; Paul Pauls; Paul Pauls; Dirk G. Dechering; Gerrit Frommeyer; Joshua I. Goldhaber; Uwe Kirchhefer; Lars Eckardt; et al. (Frontiers Media S.A., 2017)
Background/Objective: The cardiac Na+/Ca2+ exchanger (NCX) has been identified as a promising target to counter arrhythmia in previous studies investigating the benefit of NCX inhibition. However, the consequences of NCX inhibition have not been investigated in the setting of altered NCX expression and function, which is essential, since major cardiac diseases (heart failure/atrial fibrillation) exhibit NCX upregulation. Thus, we here investigated the effects of the NCX inhibitor SEA0400 on the Ca2+ transient amplitude and on proarrhythmia in homozygous NCX overexpressor (OE) and heterozygous NCX knockout (hetKO) mice compared to corresponding wild-types (WTOE/WThetKO).Methods/Results: Ca2+ transients of field-stimulated isolated ventricular cardiomyocytes were recorded with fluo-4-AM or indo-1-AM. SEA0400 (1 μM) significantly reduced NCX forward mode function in all mouse lines. SEA0400 (1 μM) significantly increased the amplitude of field-stimulated Ca2+ transients in WTOE, WThetKO, and hetKO, but not in OE (% of basal; OE = 98.7 ± 5.0; WTOE = 137.8 ± 5.2*; WThetKO = 126.3 ± 6.0*; hetKO = 140.6 ± 12.8*; *p < 0.05 vs. basal). SEA0400 (1 μM) significantly reduced the number of proarrhythmic spontaneous Ca2+ transients (sCR) in OE, but increased it in WTOE, WThetKO and hetKO (sCR per cell; basal/+SEA0400; OE = 12.5/3.7; WTOE = 0.2/2.4; WThetKO = 1.3/8.8; hetKO = 0.2/5.5) and induced Ca2+ overload with subsequent cell death in hetKO.Conclusion: The effects of SEA0400 on Ca2+ transient amplitude and the occurrence of spontaneous Ca2+ transients as a proxy measure for inotropy and cellular proarrhythmia depend on the NCX expression level. The antiarrhythmic effect of SEA0400 in conditions of increased NCX expression promotes the therapeutic concept of NCX inhibition in heart failure/atrial fibrillation. Conversely, in conditions of reduced NCX expression, SEA0400 suppressed the NCX function below a critical level leading to adverse Ca2+ accumulation as reflected by an increase in Ca2+ transient amplitude, proarrhythmia and cell death. Thus, the remaining NCX function under inhibition may be a critical factor determining the inotropic and antiarrhythmic efficacy of SEA0400.